New Light on Arrian’s Praenomen from Digital Epigraphy - Leon, Daniel W.; Rask, K. A. (Histos, 2019)
This article reconsiders the evidence for Arrian’s long-disputed praenomen using digital imaging techniques that have only recently become available. Through the application of Reflectance Transformation Imaging and 3-D scanning combined with traditional epigraphic methods, the authors clarify the text of the only inscription preserving Arrian’s praenomen, thus contributing to the body of knowledge about an important historical personage and his relationship to elite communities in the eastern Mediterranean. The uses and limitations of these technologies are discussed to illuminate their value for original epigraphic research, which, the authors argue, is greater than has generally been recognized.